Heritability of aortic valve stenosis and evidence of bicuspid enrichment in families with tricuspid aortic valve stenosis. (25th November 2020) - Boureau, A; Le Souarnec, S; Dina, C; Karakachoff, M; Capoulade, R; Piriou, N; Cueff, C; Probst, V; Schott, J.J; Le Tourneau, T
Abstract: Background: Calcific aortic valve stenosis (CAVS) is the most common valvular heart disease. Although a familial component has been described, the heritability remains unknown. This study aimed to determine the heritability of CAVS and to compare the prevalence of bicuspid aortic valve (BAV) relatives among families with tricuspid and bicuspid aortic valve phenotype and to a control cohort. Methods: Probands were recruited following aortic valve replacement in three French university hospitals. All relatives who agreed to participate were enrolled in the study. Families were defined as tricuspid aortic valve (TAV) or BAV families based on the aortic valve phenotype observed in the proband. As control group, we used probands diagnosed with mitral valve prolapse and their families. All recruited probands and relatives underwent comprehensive transthoracic echocardiography to determine aortic valve morphology and CAVS status. Additive genetic heritability was performed with SOLAR genetic statistics package. Prevalence of BAV relatives in each sub-group and Prevalence Ratio were calculated. Results: Within the 2371 relatives coming from 138 CAVS families, the heritability of CAVS was significant (h 2 =0.49, p<0.001). Furthermore, TAV stenosis heritability was only significant in TAV families (h 2 =0.20, p=0.013). The prevalence of BAV was significantly higher in TAV families and BAV families than control families (5.96 [95% CI: 4.2–8.3%], [n=32 of 537] vs. 2.49 [95% CI: 1.3–4.7%], [n=9 of 361]; PR 2.64 [95% CI: 1.41–5.91]; p=0.005 and 10.20 [95% CI: 7.0–14.5%], [n=26 of 255] vs. 2.49 [95% CI: 1.3–4.7%], [n=9 of 361]; PR 4.63 [95% CI: 2.35–13.44]; p<0.001; respectively). Conclusions: The heritability of aortic valve stenosis in this population confirms the genetic effect in determining aortic stenosis for all aortic valve phenotype and for tricuspid aortic valve. The bicuspid enrichment in TAV families suggests common genetic predisposition of aortic valve stenosis in some families. Taking all together, these findings encourage echocardiography screening of relatives of affected individuals. Funding Acknowledgement: Type of funding source: None